A SIMULTANEOUS ESTIMATION, VALIDATION AND FORCED DEGRADATION STUDIES OF 5-FLUOROURACIL AND TEGAFUR IN A PHARMACEUTICAL DOSAGE FORM USING REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD - Mistry, Vaishali; Yelwe, Akshay; Deshpande, Amey (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study describes the stability indicating reversed-phase high-performance liquid chromatography (RP-HPLC) method for simultaneous estimation of 5-fluorouracil and tegafur in pharmaceutical dosage forms. Method: 5-fluorouracil and tegafur the propose RP-HPLC method were developed by using Shimadzu Prominence-i LC-2030 HPLC system equipped with UV detector and chromatographic separation was carried on shim-pack gist c18 (250 × 4.6 mm, 5 μ) column at a flow rate of 1 ml/min and the run time was 10 min. The mobile phase consisted of methanol and water in the ratio of 50:50% v/v and elements were scanned using a UV detector at 271 nm. Result: The retention time of 5-fluorouracil and tegafur was found to be 2.74 and 3.66 min, respectively. A linearity response was observed in the concentration range of 13.4 μg/ml–31.3 μg/ml for 5-fluorouracil and 6 μg/ml–14 μg/ml for tegafur, respectively. Limit of detection and limit of quantification of 5-fluorouracil were 10.97 μg/ml and 33.26 μg/ml and for tegafur are 4.89 μg/ml and 14.83 μg/ml, respectively. Conclusion: The stability indicating that the method was developed by subjecting drugs to stress conditions such as acid and base hydrolysis, oxidation, photo and thermal degradation, and degraded products formed were resolved successfully from samples.